UMPSA organises korban and akikah in conjunction with Aidiladha - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PEKAN, 19 June 2024 – In an effort to enliven the atmosphere in conjunction with Hari Raya Aidiladha and towards the end of Tashriq day, the Islamic and Human Development Centre (PIMPIN), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) successfully carried out the korban and akikah programme.